La felicidad... ¡ese imperativo contemporáneo! : reflexiones desde las ciencias sociales y humanidades - Pattaro Amaral, Fernanda (Corporación Universitaria Americana, 2023)
This publication originates from the research project "The action of joy, happiness, contentment and rejoicing as contemporary imperatives: a factory of artificial smiles", which proposed to think about the phenomenon of the quasi-obligatory nature of being happy in order to adapt to life in contemporary society. One of its products was a lecture in the Psychology program of the same name of this publication, in the form of a conversation that brought together different specialists to discuss the topic. These same specialists were invited to elaborate the pages of this book, and others were invited to broaden the discussion. A work conceived and written by several hands.